Adolescents, sexual behaviour and implications for an epidemic of HIV/AIDS among the young. Issue 2 (April 1993) - Dickson, N; Paul, C; Herbison, P
Abstract : OBJECTIVE–To determine the patterns of sexual behaviour, condom use and sexually transmitted diseases among young New Zealanders, and the characteristics of those with many sexual partners. SUBJECTS–A cohort of young people enrolled in a longitudinal cohort study, and followed up since age three. METHODS–Subjects were interviewed at age 18 years as part of a multidisciplinary health and development study. Questions about sexual behaviour were presented by computer. RESULTS–Overall 862/1027 (83.9%) surviving in the cohort was interviewed. Only 1.4% declined to answer the section on sexual behaviour. Sexual intercourse in the previous 12 months was reported by 57.6% of the young men and 67.9% of the young women. Amongst those who were sexually active more of the young men reported multiple partners than the young women (59.8% v 46.5% p < 0.001). There was a trend for increasing number of partners with indices of lower school achievement but no significant association with socio-economic status. Condom use decreased with increasing number of partners for the young women, and for the young men there was no association. Sexually transmitted diseases were reported more commonly with increasing number of sexual partners for both men and women. The rates of sexual activity were substantially higher than reported in a comparable survey 20 years ago. CONCLUSIONS–The pattern of sexual behaviour and condom use, and the occurrence of sexually transmitted diseases in this sample give cause for concern about the spread of sexually transmitted diseases including the possibility of an epidemic of HIV among heterosexual young people in New Zealand. The findings should help in targeting health promotional activities within this age group.